Xarxes semàntiques en el lèxic disponible de València. Una aproximació al lexicó bilingüe - Gómez-Devís, M-Begoña; Rodrigo, Francesc Llopis (Studia Romanica Posnaniensia, 2016)
This work deals with the situation of languages in contact and explores the nature of bilingual lexicon by studying lexical availability. Based on the results published in 2010 in Lèxic disponible de València, and in relation to ‘town’ as the center of interest, the study applied a new analytical tool called DispoGrafo, which enabled us to observe issues related to the construction and organization of the mental lexicon, for example, the incidence or profitability of facilitating semantic–priming–in clusters made up of three or more closely linked elements. The sample was obtained from 464 high school students of 2nd baccalaureate in the Valencia province, and was established to represent the ‘normal language’ variable. Two subgroups were formed: valencià-L1 (253 students) and valencià-L2 (211 students).